Dissemination of NDM-1-producing Pseudomonas aeruginosa ST308 and ST274 high-risk clones in Argentina - Rapoport, Melina (2025)
Objective: This study describes the phenotypic, molecular, and genomic characterisation of emerging blaNDM-1-producing Pseudomonas aeruginosa in Argentina, mainly driven by ST308 and ST274 clones. Methods: Nineteen clinical isolates submitted to the National and Regional Reference Laboratory on Antimicrobial Resistance between 2018 and 2024 from nine hospitals were analysed. Antimicrobial susceptibility and carbapenemase activity were evaluated. In-house PCR assays were used to detect relevant resistance determinants. Genetic relatedness was assessed by SpeI-PFGE, and whole-genome sequencing was performed on nine isolates using Illumina and Oxford Nanopore technologies. Results: All isolates were resistant to all β-lactams tested, except two, M28149 and M28715, that remained susceptible to aztreonam. All carried blaNDM-1. PFGE identified six pulsotypes, with 13 isolates in one dominant type. Whole-genome sequencing revealed six ST308, two ST274, and one ST3243; five ST308 isolates also harboured the rmtD 16S methylase gene. Phylogenetic analysis of ST308 isolates showed they formed a distinct cluster compared with those from other countries. Conclusions: The emergence of blaNDM-1-producing P. aeruginosa associated with ST308 and ST274 clones represents a public health concern, particularly given the scarcity of effective treatment options for severe infections caused by these high-risk clones.